Impact of Social Media on Self-Esteem Among Nursing Students - Arora, Kritika; Gupta, Ravinder Kumar; Gupta, Urvi; Babber, Sunny; Moza , Indra (Indian Journal of Child Health, 2024)
Introduction: The rise of social media has transformed communication dynamics, particularly among nursing students who utilise these platforms for social interaction and academic collaboration. While social media can enhance self-esteem through connection and validation, it also presents risks associated with negative social comparisons, particularly for students under academic stress. Materials and Methods: This cross-sectional study included 185 nursing students from a college, with 160 consenting to participate. Data were collected through an online survey comprising a demographic questionnaire, the Social Networking Use Questionnaire (Gupta & Bashir), and the Rosenberg Self-Esteem Scale. Statistical analyses were conducted using IBM SPSS version 21, employing independent t-tests, ANOVA, and Pearson correlation coefficients. Results: The participants' mean age was 18.76 years, with an average social media usage of 5.24 hours daily. Results indicated a strong correlation between time spent on social media and self-esteem (r = 0.342, p < 0.01), while social interaction showed a weaker correlation (r = 0.233, p < 0.01). Notably, entertainment and informativeness dimensions did not significantly correlate with self-esteem (r = 0.092, p = 0.861; r = 0.061, p = 0.923). Discussion: The findings reveal a complex relationship between social media use and self-esteem. While social media provides valuable opportunities for connection and information, excessive use can lead to negative self-perceptions. The lack of strong correlations between self-esteem and dimensions like informativeness and entertainment suggests that while these elements are enjoyable, they do not significantly enhance self-worth. Conclusions: This study highlights the nuanced impact of social media on nursing students' self-esteem. Future research should investigate conditions that promote positive self-worth versus those that exacerbate negative feelings, informing strategies to foster healthier social media engagement among students.